Pelatihan Bisnis Plan dan Digitalisasi Marketing - Maria Silvana Mariabel Carcia; Cicilia Ayu Wulandari Nuwa; Maria Nona Dince; Dimas Relino (BADAN PENERBIT STIEPARI PRESS, 2024)
Some of the indicators that can be used today include the increase in digital advertising spending, the growth of smartphone ownership that provides easy inter-net access, the improvement of telecommunications infrastructure in order to improve the quality of data access, and the launch of 4G services.